Design of A Win-Win Big Data Financial Management Platform For Small and Medium-Sized Enterprises - Lu, Fang (International Journal of Management and Education in Human Development, 2022)
With the development of 5g technology, the network transmission speed and stability have been greatly improved, ensuring the arrival of the big data era. This paper is a win-win platform model to solve the financial development dilemma of small and medium-sized enterprises by using big data technology to train accounting students according to the training situation of Chinese accounting majors and the development dilemma of small and medium-sized enterprises.